Freeway intelligent transportation oriented wireless access technologies evaluation - Shang-jing LIN; Jin TIAN; Jin-hong LI (物联网学报, 2017)
The popularization of broadband mobile communication technology has paved a way for the development of intelligent transportation industry.At the meantime,the intelligent transportation system (ITS) has also put forward higher requirements for the broadband mobile communication technologies.Based on the summary of the challenges faced by the broadband mobile communication technologies when applied to ITS,two typical expressway communication scenarios are selected in which the performance of wireless access technologies are evaluated and compared.It can provide theoretical reference for the development of ITS.